The quest for accountability: Parliament and public administration in Bangladesh - Nizam Ahmed; Aftab Ahmed (1996)
This article examines the scope and limits of parliamentary control over public administration in Bangladesh. It adopts a comparative approach, focusing on the use of surveillance techniques by members of Bangladesh's first, second, and fifth parliaments. The evidence presented here shows that the three JSs, as a natural rule, have fared differently in scrutinising the activities of the government and administration. But the data do not always reveal any positive correlation between the nature of partisanship and the performance of the parliament in overseeing governmental activities. Furthermore, the various surveillance techniques do not generally appear to be very effective in probing into the operations of the government. Two factors that account for this are first, the intransigent attitude of the bureaucracy; and second, the lack of willingness and ability of MPs to seriously enquire into government policies and operations. The article suggests that the traditional control mechanisms be supplemented by new measures; otherwise the quest for accountability may remain elusive
Keywords: Public administration - Bangladesh; Public administration